Crown closure affects endophytic leaf mycobiome compositional dynamics over time in Pseudotsuga menziesii var. menziesii. (June 2022) - Gervers, Kyle A.; Thomas, Daniel C.; Roy, Bitty A.; Spatafora, Joseph W.; Busby, Posy E.
Abstract: Old-growth Pseudotsuga menziesii var. menziesii forests produce complex environmental and spatial gradients along which biota assemble. Given this, it has been proposed that changes in the crown microenvironment are associated with different community assembly outcomes for needle fungi. Using high-throughput sequencing, the endophytic mycobiomes of needles were characterized for increasing ages of needles sampled along the boles of eight coastal Douglas-fir trees. Leveraging airborne light detection and ranging (LiDAR) data to create three-dimensional "point cloud" representations of tree crowns revealed that crown closure accounted for more fungal compositional variation than height in crown, and fungal richness and diversity were positively correlated with increasing crown closure. Supplementing the point clouds of each climbed tree with clouds from >5, 000 randomly selected trees in the study area showed that fungal communities from closed portions of the crown were increasingly structured with needle age. These findings highlight the importance of the crown microenvironment in the development of foliar fungal communities for a foundation tree species. Highlights: LiDAR-derived crown closure accounts for more compositional variation than height. The influence of crown closure on composition and richness depends on needle age. The community structures of open and closed exposures diverge for older needles.